PERBANDINGAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL DISCOVERY LEARNING DAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) PADA MATERI PELUANG KELAS VI SEKOLAH DASAR - Ursila, Reti; Adi Pangestu, Reza; Sintia; Setiawati, Ina; Verawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to compare student learning outcomes through the Discovery Learning model and the Cooperative Learning model of Teams Games Tournament (TGT) type on probability material in Grade VI elementary school. The research approach used is quantitative with an experimental method and within-subject design (repeated measures), where the same group of students received two sequential learning treatments. The research was conducted at SDN 6 Purwawinangun with a total of 23 students as research subjects using total sampling technique. The first treatment applied the Discovery Learning model on fair and unfair game comparison material, followed by a posttest. The second treatment applied the TGT model on probability comparison material for decision-making, followed by a second posttest. Data were collected through written tests and analyzed using SPSS. Descriptive statistics showed that the mean score of the Discovery Learning group was 73.91 (SD = 18.77), while the TGT group obtained a mean score of 81.30 (SD = 9.20). The Shapiro-Wilk normality test on the difference scores produced W = 0.924 with p = 0.081, indicating that the data was normally distributed. Therefore, the Paired Sample t-Test was used as the hypothesis testing, resulting in t-count = 2.494 with p = 0.021 (p < 0.05). The results showed that there was a statistically significant difference in student learning outcomes between the two models. The TGT model produced higher and more consistent learning outcomes compared to the Discovery Learning model. These findings suggest that collaborative and game-based learning approaches such as TGT can be more effective in improving elementary school students' understanding of probability concepts.